Uncertainties in the Contemporary Political Landscape of West Africa amidst Global and Regional Challenges - Terzungwe, Daniel Kumafan; Ahmed, Tijjani; Oluwaseun, Owolabi Olayinka (American Journal of International Relations, 2024)
Purpose: This paper analyzes the political instability in West Africa, exploring how historical legacies, military coups, and insurgent violence contribute to this instability. It also examines the role of external geopolitical influences and the limitations faced by regional organizations like ECOWAS in fostering stability. Materials and Methods: The research adopts a historical and analytical approach, examining the colonial legacies, recent military coups in countries such as Mali, Burkina Faso, and Guinea, and the rise of armed insurgent groups. It also investigates the external influences of powers like Russia and China, alongside regional efforts by ECOWAS to manage the political situation. Findings: The research highlights that the persistence of military coups and insurgent violence is deeply rooted in the colonial past and exacerbated by weak democratic institutions. The resurgence of military coups underscores the fragility of governance in the region, while the proliferation of armed groups intensifies security threats. External geopolitical actors such as Russia and China have reshaped political alliances in the region, complicating ECOWAS' efforts to foster cooperation. Implications to Theory, Practice and Policy: To achieve lasting political stability, West Africa needs to strengthen its democratic institutions, promote regional cooperation, and develop more effective strategies to counteract both internal security threats and external geopolitical influences. ECOWAS must enhance its capacity to mediate conflicts and unify states amidst growing geopolitical divides.